Legal Strength on the Minute of Meeting Made by a Notary to Shareholders Through the Online System (Teleconference) - Widya Islamiyah; Maskun Maskun; Wiwie Heryani (Universitas Medan Area, 2022)
This study aims to: 1) Assess the legal strength of the minutes of meetings made by a notary to shareholders through the online system (Teleconference); 2) To check that the deed of the minutes of the meeting made by a notary to the shareholders through the online system (teleconference) is in accordance with the principle of professionalism as regulated in Law no. 2 of 2014 in conjunction with Law no. 30 of 2004 concerning the Position of a Notary. This type of research is normative legal research, namely by reviewing materials from various laws and regulations and other supporting materials from various literatures related to the problem. Non-legal materials obtained using a conceptual approach carried out at Notary and/or PPAT offices in Makassar City through interviews. Then the legal and non-legal materials are analyzed using qualitative methods, namely analyzing legal materials related to the problem under study and the results obtained are described descriptively, namely by describing, explaining and describing according to the problems in this study, conclusions will then be drawn. The results of this study indicate that: 1) The legal force of the deed of minutes of the GMS by a notary through the online teleconference system can be seen in Article 77 of the Company Law which allows that the GMS can be held via teleconference. The implementation of the GMS through teleconference has binding legal force for all parties. However, the implementation of the GMS by teleconference has several drawbacks such as not having a quorum while the rules at the GMS must all be present, the network/internet connection is usually disrupted, the signature on the attendance list in the evidence can be denied, and then there can be forgery of faces or clothes. 2) In terms of conformity with the deed of minutes of the GMS via teleconference which is connected with the principle of professionalism, there are differences of opinion between the notaries, namely, in looking at articles such as Article 77 and Article 76 paragraph (4), namely if the GMS is present and/or represented by all shareholders and all shareholders agree to hold a GMS with a certain agenda, the GMS can be held anywhere with due observance of the provisions as referred to in paragraph (3 ). Based on these rules, it is possible to have conformity with the principles of professionalism of the UUJN.